A Comparative Analysis: Linking Adverbials in Learners’ Academic Writing - Akhlisa Ainun Nizar; Iis Badriatul Munawaroh (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
This study examines the frequency and usage patterns of linking adverbials (LAs) in Indonesian EFL learners’ essay writing in comparison with those of native speakers. The ICNALE corpus is used as a source for the learner and reference corpora: Indonesian EFL learners and native speakers’ themed essays, each consisting of 100 essays. The sub-categorizations of LAs adopted Celce-Murcia and Larsen-Freeman’s (1999) where they are divided into: additive (in addition, besides, furthermore), adversative (however, in contrast, actually), causal (therefore, consequently, in that case), and sequential (first, last, second). The results found a similar distribution in the usage frequency of linking adverbials. Further analysis discovered a significant overuse in additive LA also and underuse causal LA on the other hand. A more detailed and comprehensive investigation of why such things are apparent found similar misuse cases to previous research, one of them is the lack of understanding in semantic properties. On the basis of the findings, a number of pedagogical implications can be taken.